Potential contribution of anti-p200 autoantibodies to mucosal lesions in anti-p200 pemphigoid - Gao, Yangmin; Qian, Hua; Hashimoto, Takashi; Li, Xiaoguang (Frontiers in Immunology, 2023)
Anti-p200 pemphigoid is a relatively rare subepidermal autoimmune bullous disease (AIBD), which was firstly reported by Detlef Zillikens, Takashi Hashimoto and others in 1996. Skin lesions are considered as the major clinical features of this disease, with occasional involvement of mucosal lesions. The mechanism of mucosal lesions involved in anti-p200 pemphigoid is still unclear. In the present study, we aimed to analyze published data on cases and case series of anti-p200 pemphigoid with mucosal lesions and explored the potential contribution of anti-p200 autoantibodies to mucosal lesions. A total of 32 papers that comprised 52 anti-p200 pemphigoid patients with various mucosal lesions were included in this review. Oral lesions were involved in 75.0% patients, followed by genital lesions (26.9%) and ocular lesions (11.54%). Only one patient had psoriasis, 26.9% patients had multiple mucosal lesions, and 30.8% cases had comorbidity of other AIBDs, particularly anti-laminin (LM) 332-type mucous membrane pemphigoid (MMP). In comparison with anti-LM332-type MMP, anti-BP180-type MMP and epidermolysis bullosa acquisita, higher frequency of genital lesions was identified as a unique character of anti-p200 pemphigoid with mucosal lesions. These results indicated that anti-p200 autoantibodies might contribute to mucosal lesions in a pattern different from other MMP-related autoantibodies, although its pathogenetic mechanisms are still unclear.